The Role of Competence, Psychological Capital, and Intrinsic Motivation Interventions in Influencing Teacher Performance in the Era of the COVID-19 Pandemic - Diarta, Luthfita Ayu; Saluy, Ahmad Badawy (International Journal of Law Policy and Governance, 2022)
Article history:Received: Revised: Accepted: Keywords: Competence, Psychological Capital, Intrinsic Motivation, Teacher PerformancePurpose – This research aims to determine the role of competence and psychological capital and their impact on teacher performance directly or indirectly via intrinsic motivation, especially during the COVID-19 pandemic era. Methodology/approach – This research method is causal quantitative using a saturated sample of 121 teachers at SD Yayasan Al Azhar Lampung. Using SEM-PLS as a data analysis method with the SmartPLS 3.2.9 application. Findings – It found a positive and significant role of competency on teacher performance, competency on intrinsic motivation, psychological capital on intrinsic motivation, and intrinsic motivation on teacher performance. Then, the role of psychological capital is not positive and not significant for teacher performance. Also, the indirect relationship formed from this research path is that intrinsic motivation plays a positive and significant role in the relationship between teacher competence to teacher performance, and intrinsic motivation plays a positive and significant role in the relationship between psychological capital and teacher performance. Novelty/value – Motivation intrinsic proven that it can intervene between psychological and teacher performance. Cause without intrinsic motivation, psychological capital hasn't impact on teacher performance.